Keterampilan Bahasa Inggris yang dibutuhkan Guru-guru SMA RSBI Kota Padang - Zul Amri (International Conference on Languages and Arts, 2012)
RSBI SMA teachers are required to be able to teach their subjects using English as the medium of instruction. As the result, they need to improve their English. They went to English courses available in their surroundings. They were taught by the English instructor from the English course without considering their needs for the language skills. The data collected from SMAN1 and SMAN 10 Padang indicate that they need the four skills of English with different order of needs. Speaking skill appeared to be the most needed skill followed by listening, writing, and reading skills. It means that the speaking skill should have the biggest portion and the most emphasis in the implementation of the English training for the RSBI SMA teachers.